(untitled) (American Journal of Islam and Society, 1996)
Living memory has now faded concerning the scattered pieces of empire that Britain ruled in East Africa and South and East Arabia for up to a quarter of a century after the end of the Second World War. In the nottoo- distant future, what Elizabeth Monroe once described felicitously as Britain’s "moment" in the Middle East will have passed from personal recollection into history. Mindful of that inevitability, British diplomat and quondam scholar Glen Balfour-Paul has undertaken to chronicle the postwar encounter between Britishers and Arabs in Sudan, Aden, and the Gulf states from which Britain withdrew in 1956, 1967, and 1971, respectively. The results of his study should be of particular interest to government officials requiring perspective for the formulation of policy and to neophyte foreign service officers about to depart for the regions discussed, as well as to scholars and advanced students of the contemporary Middle East. To his subject, Balfour-Paul brings almost unique credentials. After experience in the Middle East during the Second World War, he became a member of the Sudan Political Service for nine years and, thereafter, served as a diplomat until 1977 in various Arab countries, in three of them as ambassador. The book under review was written largely in the late 1980s while the author was an honorary research fellow at the Centre for Arab Gulf Studies at Exeter University. In the meticulousness of its research, the objectivity demonstrated on contested issues, and above all in the elegance of its prose, the volume at hand is a model of what diplomatic history (a craft now rarely practiced by professional historians) should be. Those on both sides of the British-Arab divide have reason to be grateful that there is ...